Successive application of the layer-related CFP method for internal multiple removal. (31st March 2015) - Jiawen, Song; Verschuur, Eric; Bo, Zhao; Hequn, Li
Abstract: Internal multiples are very difficult to remove due to their complex raypaths and poor velocity discrimination with primaries. The layer-related common focus point (CFP) method has proven to be effective for internal multiple removal, however, single application leads to multiple leakage when there are several strong reflecting boundaries in the subsurface. In order to reduce this leakage, we propose successive application of the layer-related CFP method for internal multiple removal through cascaded processing of several time levels. In this paper, we concisely reformulate the theory of the boundary- and layer-related CFP methods and compare their robustness to velocity errors. For the layer-related version in particular, we illustrate the specific steps of the method using synthetic data examples. Finally, the successive layer-related CFP method is tested on Mississippi Canyon field data.